tìm x:
a) 5x . 5 = 625
b) 3x = 9.27
c) (x-6)2 = 9
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\Leftrightarrow\left(2x-3\right)\left(x+2\right)=0\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{2}\\x=-2\end{matrix}\right.\\ b,\Leftrightarrow x^3-27-x^3+4x=1\\ \Leftrightarrow4x=28\Leftrightarrow x=7\\ c,\Leftrightarrow4x^2-4x-8=0\\ \Leftrightarrow x^2-x-2=0\\ \Leftrightarrow\left(x-2\right)\left(x+1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=-1\end{matrix}\right.\\ d,\Leftrightarrow2x^2+6x+x+3=0\\ \Leftrightarrow\left(x+3\right)\left(2x+1\right)=0\Leftrightarrow\left[{}\begin{matrix}x=-3\\x=-\dfrac{1}{2}\end{matrix}\right.\)
\(a,\) \(5x\left(4-x\right)+\left(5x^2-12\right)=x+6\)
\(< =>20x-5x^2+5x^2-12-x-6=0\)
\(< =>19x-18=0\)
\(< =>x=\dfrac{18}{19}\)
\(b,\left(2x-7\right)\left(5+4x\right)-8\left(x^2-4x+5\right)=-30\)
\(< =>10x+8x^2-35-28x-8x^2+24x-40+30=0\)
\(< =>6x-45=0< =>x=\dfrac{45}{6}=7,5\)
a) \(5x\left(4-x\right)+\left(5x^2-12\right)=x+\Rightarrow6\\ \Leftrightarrow20x-5x^2+5x^2-12=x+6\\ \Leftrightarrow20x-12=x+6\\\Rightarrow20x-x=6+12\\ \Rightarrow19x=18\\ \Rightarrow x=\dfrac{18}{19}\)
b) \(\left(2x-7\right)\left(5+4x\right)-8\left(x^2-3x+5\right)=-30\\ \Rightarrow10x+8x^2-35-28x-8x^2+24x-40=-30\\ \Rightarrow6x-75=-30\\ \Rightarrow6x=45\\ \Rightarrow x=\dfrac{15}{2}\)
a. (3x - 1).(2x + 7) - (x + 1).(6x - 5) = 16
<=> 6x^2 + 19x - 7 - (6x^2 + x - 5) = 16
<=> 18x - 2 = 16
<=> 18x = 18
<=> x = 1
b. (10x + 9).x - (5x - 1).(2x + 3) = 8
<=> 10x^2 + 9x - (10x^2 + 13x - 3) = 8
<=> -4x + 3 = 8
<=> -4x = 5
<=> x = -5/4
c. (3x - 5).(7 - 5x) + (5x + 2).(3x - 2) - 2 = 0
<=> -15x^2 + 46x - 35 + 15x^2 - 4x - 4 - 2 = 0
<=> 42x - 41 = 0
<=> x = 41/42
`a)16x^2-24x+9=25`
`<=>(4x-3)^2=25`
`+)4x-3=5`
`<=>4x=8<=>x=2`
`+)4x-3=-5`
`<=>4x=-2`
`<=>x=-1/2`
`b)x^2+10x+9=0`
`<=>x^2+x+9x+9=0`
`<=>x(x+1)+9(x+1)=0`
`<=>(x+1)(x+9)=0`
`<=>` \(\left[ \begin{array}{l}x=-9\\x=-1\end{array} \right.\)
`c)x^2-4x-12=0`
`<=>x^2+2x-6x-12=0`
`<=>x(x+2)-6(x+2)=0`
`<=>(x+2)(x-6)=0`
`<=>` \(\left[ \begin{array}{l}x=-2\\x=6\end{array} \right.\)
`d)x^2-5x-6=0`
`<=>x^2+x-6x-6=0`
`<=>x(x+1)-6(x+1)=0`
`<=>(x+1)(x-6)=0`
`<=>` \(\left[ \begin{array}{l}x=6\\x=-1\end{array} \right.\)
`e)4x^2-3x-1=0`
`<=>4x^2-4x+x-1=0`
`<=>4x(x-1)+(x-1)=0`
`<=>` \(\left[ \begin{array}{l}x=1\\x=-\dfrac14\end{array} \right.\)
`f)x^4+4x^2-5=0`
`<=>x^4-x^2+5x^2-5=0`
`<=>x^2(x^2-1)+5(x^2-1)=0`
`<=>(x^2-1)(x^2+5)=0`
Vì `x^2+5>=5>0`
`=>x^2-1=0<=>x^2=1`
`<=>` \(\left[ \begin{array}{l}x=1\\x=-1\end{array} \right.\)
a) \(\sqrt{x-3}>2\left(đk:x\ge3\right)\)
\(\Leftrightarrow x-3>4\Leftrightarrow x>7\)
b) \(\sqrt{36x^2-12x+1}=5\)
\(\Leftrightarrow\sqrt{\left(6x-1\right)^2}=5\)
\(\Leftrightarrow\left|6x-1\right|=5\)
\(\Leftrightarrow\left[{}\begin{matrix}6x-1=5\\6x-1=-5\end{matrix}\right.\)\(\Leftrightarrow\left[{}\begin{matrix}x=1\\-\dfrac{2}{3}\end{matrix}\right.\)
c) \(\sqrt{9\left(5x^2-2x+16\right)}=3x+12\left(đk:x\ge-4\right)\)
\(\Leftrightarrow9\left(5x^2-2x+16\right)=9x^2+72x+144\)
\(\Leftrightarrow36x^2-90x=0\)
\(\Leftrightarrow18x\left(2x-5\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\left(tm\right)\\x=\dfrac{5}{2}\left(tm\right)\end{matrix}\right.\)
a) \(\left(x-2\right)^2-\left(x^2-3x\right)=9\)
\(\Rightarrow x^2-4x+4-x^2+3x-9=0\)
\(\Rightarrow-x-5=0\)
=> x = -5
b) \(\left(5x-2\right)^2=\left(4-x\right)^2\)
\(\Rightarrow25x^2-10x+4-16+8x-x^2=0\)
\(\Rightarrow24x^2-2x-12=0\)
\(\Rightarrow12x^2-x-6=0\)
\(\Rightarrow\left[{}\begin{matrix}x=-\dfrac{2}{3}\\x=\dfrac{3}{4}\end{matrix}\right.\)
c) \(x^2-4x-5=0\)
=> (x - 5).(x + 1) = 0
=> x = 5 hoặc x = -1
a: \(\Leftrightarrow-2x=-\dfrac{1}{3}-\dfrac{1}{8}-\dfrac{5}{7}=-\dfrac{197}{168}\)
hay x=197/336
c: \(\Leftrightarrow5x=9+\dfrac{6}{18}-\dfrac{2}{7}=\dfrac{190}{21}\)
hay x=38/21
a) \(5^x.5=625\)
\(\Rightarrow5^x=125=5^3\)
\(\Rightarrow x=3\)
b) \(3^x=9.27\)
\(\Rightarrow3^x=3^2.3^3=3^5\)
\(\Rightarrow x=5\)
c) \(\left(x-6\right)^2=9\) .
\(\Rightarrow\orbr{\begin{cases}x-6=-3\\x-6=3\end{cases}}\Rightarrow\orbr{\begin{cases}x=3\\x=9\end{cases}}\)
5x.5=625
=>5x.5=54
=>5x=54:5
=>5x=54-1
=>5x=53
=>x=3